Economic considerations on the usage of biologics in the allergy clinic. Issue 1 (6th September 2020) - Azzano, Pauline; Dufresne, Élise; Poder, Thomas; Bégin, Philippe
Abstract: The advent of biologic therapies has transformed care for severe atopic disorders but their high cost poses new challenges with regard to long‐term sustainability and fair allocation of resources. This article covers the basic concepts of cost‐utility analyses and reviews the available literature on cost utility of biologic drugs in atopic disorders. When used within their limits as part of a multi‐dimensional assessment, economic analyses can be extremely useful to guide decision‐making and prioritization of care. Despite the good quality of most cost‐utility analyses conducted for the use of biologics in asthma and other atopic diseases, their conclusions regarding cost‐effectiveness are extremely variable. This is mainly due to the use of inconsistent estimates of health utility benefit with therapy. Development of reliable and validated instruments to measure disutility in atopic disorders and measure of indirect costs in atopic disease are identified as a priority for future research.